(untitled) (De Legibus - Law Journal, 2024)
This review focuses on the work Doppelindividualiserung und Irrtum. Studien zur strafrechtlichen Lehre von der Erfolgszurechnung zum Vorsatz, by Yu An Hsu. The objections raised by Hsu against the dominant doctrine regarding the solutions to cases of mistake (error in persona, aberratio ictus, and error about the causal process) are examined, specifically focusing on cases of mistake involving double individualization. Finally, Hsu’s proposed solution is critically analyzed, with particular attention given to the categories of abstract knowledge and dolus indirectus, upon which the author bases his approach to resolving various cases of mistake.